Challenges of the Republic of Indonesia’s Passport Services from Quality of Government Perspectives - Bawono, Sri Kuncoro; Aji, Koesmoyo Ponco; Wiraputra, Anindito Rizki; Astuti, Rita Kusuma (Journal of Governance, 2025)
Providing better public services has become the main task of the Indonesian government. In terms of passport services, the Indonesian government, through the Directorate General of Immigration, has made efforts to improve passport services for all Indonesian citizens. The Directorate General of Immigration has introduced some programs to provide a better passport service. However, the government was still facing some challenges if considered through the quality of government perspectives. This paper will reveal some challenges that are faced by the government in terms of the quality of government, including the absence of corruption, the rule of law, and impartiality. As a result, the Directorate General of Immigration is on the right track to provide quality passport services by implementing some innovations. Nevertheless, the government still needs to work on the anti-corruption programs.